Serial measurement of presepsin, procalcitonin, and C-reactive protein in the early postoperative period and the response to antithymocyte globulin administration after heart transplantation - Franeková, Janka; Sečník, Peter; Lavríková, Petra; Kubíček, Zdenek; Hošková, Lenka; Kieslichová, Eva; Jabor, Antonín (Clinical transplantation, 2017)
Differentiation between systemic inflammatory response syndrome and sepsis in surgical patients is of crucial significance. Procalcitonin (PCT) and C-reactive protein (CRP) are widely used biomarkers, but PCT becomes compromised after antithymocyte globulin (ATG) administration, and CRP exhibits limited specificity. Presepsin has been suggested as an alternative biomarker of sepsis. This study aimed to demonstrate the role of presepsin in patients after heart transplantation (HTx). Plasma presepsin, PCT, and CRP were measured in 107 patients serially for up to 10 days following HTx. Time responses of biomarkers were evaluated for both noninfected (n=91) and infected (n=16) patients. Areas under the concentration curve differed in the two groups of patients for presepsin (P<.001), PCT (P<.005), and CRP (P<.001). The effect of time and infection was significant for all three biomarkers (P<.05 all). In contrast to PCT, presepsin was not influenced by ATG administration. More than 25% of noninfected patients had PCT above 42 μg/L on the first day, and the peak concentration of CRP in infected patients was reached on the third post-transplant day (median 135 mg/L). Presepsin seems to be as valuable a biomarker as PCT or CRP in the evaluation of infectious complications in patients after HTx.
Keywords: Lipopolysaccharide Receptors; dospělí; Communicable Diseases; Prognosis; studie případů a kontrol; imunosupresiva; Humans; lipopolysacharidové receptory; následné studie; lidé středního věku; Middle Aged; transplantace srdce; Peptide Fragments; prognóza; Follow-Up Studies; antilymfocytární sérum; Risk Factors; mužské pohlaví; infekční nemoci; kalcitonin; Adult; Graft Survival; Calcitonin; rizikové faktory; peptidové fragmenty; Postoperative Complications; biologické markery; C-reaktivní protein; ženské pohlaví; pooperační komplikace; přežívání štěpu; Immunosuppressive Agents; lidé; C-Reactive Protein; Case-Control Studies; Biomarkers; Male; Heart Transplantation; Antilymphocyte Serum; Female